2022
DOI: 10.1007/s00442-022-05261-1
|View full text |Cite
|
Sign up to set email alerts
|

Species accumulation in small–large vs large–small order: more species but not all species?

Abstract: Although groups of small habitat patches often support more species than large patches of equal total area, their biodiversity value remains controversial. An important line of evidence in this debate compares species accumulation curves, where patches are ordered from small–large and large–small (aka ‘SLOSS analysis’). However, this method counts species equally and is unable to distinguish patch size dependence in species’ occupancies. Moreover, because of the species–area relationship, richness differences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 64 publications
1
13
0
Order By: Relevance
“…Thus, the use of species accumulation curves does not fully account for the scale dependence of species richness. As a consequence, through the effects of the species–area relationship, the probability of encountering new species is maximized when going from small-to-large parks and minimized when going from large-to-small parks [6], which results in an almost vertical slope of the initial small-to-large species accumulation curves (see electronic supplementary material, appendix S1). Our approach removed the steepest portion of the small-to-large species accumulation curve.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the use of species accumulation curves does not fully account for the scale dependence of species richness. As a consequence, through the effects of the species–area relationship, the probability of encountering new species is maximized when going from small-to-large parks and minimized when going from large-to-small parks [6], which results in an almost vertical slope of the initial small-to-large species accumulation curves (see electronic supplementary material, appendix S1). Our approach removed the steepest portion of the small-to-large species accumulation curve.…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies confirmed the prevalence of SS > SL across taxa and geographical regions [5]. These findings, however, have been criticized as misleading due to methodological concerns regarding empirical SLOSS comparisons including the use of cross-scale species accumulation curves [6]. Nevertheless, the application of the SL > SS principle remains a dominant paradigm in conservation planning and management where large patches of natural habitat are often preserved at the expense of small patches [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although the FragSAD studies are heterogeneous in design (e.g., sampling effort and method), the database includes information on the species abundance distribution sampled in each patch from each data set, thereby allowing one to control sampling effort effects while synthesizing disparate data sets. This is important because sampling effort can cause bias in SLOSS analyses, specifically by inflating biodiversity in sets of many small patches when sampling intensity across patches is not proportional to patch area (Deane, 2022; Fahrig, 2020; Gavish et al., 2012).…”
Section: Methodsmentioning
confidence: 99%
“…Empirical evidence suggesting that SS > SL could be a ubiquitous pattern elicits the question of whether this pattern can safely inform habitat protection decisions in understudied systems (Fahrig et al., 2022). However, skepticism persists around using the SS > SL pattern in conservation (Deane, 2022; Fletcher et al., 2018; Haddad et al., 2015). One reason underlying this might be that some studies suggest sensitivity to habitat fragmentation in some taxa.…”
Section: Introductionmentioning
confidence: 99%
“…where (e.g., Chase et al, 2020;Deane, 2022;Fahrig, 2017;Gooriah et al, 2021). Counter-intuitively, the area for unbiased species representation was largest for invertebrates and smallest for nonavian vertebrates.…”
Section: Variation In Response Among Metacommunity Types and Taxonomi...mentioning
confidence: 99%